Invertible networks or partons to detector and back again - Bellagente, Marco; Butter, Anja; Kasieczka, Gregor; Plehn, Tilman; Rousselot, Armand; Winterhalder, Ramon; Ardizzone, Lynton; Köthe, Ullrich (SciPost physics, 2020)
SciPost Journals Publication Detail SciPost Phys. 9, 074 (2020) Invertible networks or partons to detector and back again